Exploring the Dynamics of Athletes’ Enjoyment and Self-Determined Motivation, and of the Motivational Climate in Youth Football: A Longitudinal Perspective - Rodrigues, Filipe (2023)
We aimed to explore a short period longitudinal interplay between athletes’ enjoyment and their self-determined motivation and motivational climate in youth football. We recruited 109 youth football athletes (79 males, 30 females) through a convenient sampling method. We included individuals within the 12–17-year-old age range, with a mean age of 14.31 (SD = 1.46) years. To examine these proposed associations, we performed hierarchical multiple regression analyses and found that enjoyment at pre-season assessment (T1) and self-determined motivation and a task-involving sport climate at mid-season (T2) were significant predictors of mid-season enjoyment (at T2). However, self-determined motivation and task-involving climate at T1 did not significantly contribute to the model. These findings emphasize the importance of initial enjoyment and an evolved self-determined motivation, and task-involving climate in understanding later enjoyment in sport. Coaches, practitioners, and policymakers should prioritize strategies that enhance intrinsic motivation, provide opportunities for autonomy, and cultivate a supportive and growth-oriented environment.